New intellectual horizons in education II - Hussien, Suhailah (s.n, 2012)
This book presents the selected works of the Institute of Education academic staff in education. The purpose of this book is twofold: first to introduce to the larger public the contribution to knowledge that the graduate have made and second, by drawing attention to the work of students to make a case for the quality of work the faculty member of the Institute of Education have been and are engaged in. The book compiles the students works in Islamization of education.